Sistem Penyimpanan Arsip Dinamis Di Pusat Arsip Balai Bahasa Padang - Munawarah, Septia; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper focuses on the storage system records in Padang Language Center Archive Center. This study aims to reveal: (1) describe the records storage system suitable for Language Center Archive Center Padang. (2) identify any obstacles encountered. Data were collected through observation and interviews and data collection done deskriktif. Based on data analysis, concluded the following. First, archival storage systems in the Central Hall of Records Padang language is not in accordance with the existing procedures, the storage system is applied only on the incoming and outgoing mail. Second, the constraints faced by the Language Center are: (1) archival storage system that is incompatible with the existing theory and archives stored procedures wrong. Records received by agencies tend not to perform routine inspections and record-keeping, so the archives are not known to exist. (2) archival storage procedures are not appropriate, resulting in kesimpang crux of the existence of archives, archival storage procedures should be in accordance with proper storage procedures in accordance with the theory. (3) the lack of facilities and infrastructure used, the efforts made by the Language Center to overcome that last save point menyedikan decent archives like folders, guide, filling cabinet. Keywords: archival storage systems; central hall of records